2010
DOI: 10.1371/journal.pone.0015791
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Nasal Colonization with Methicillin-Resistant Staphylococcus aureus in Children: 2004-2009

Abstract: Background Staphylococcus aureus is an important cause of infection, particularly in persons colonized with this organism. This study compared the annual prevalence and microbiological characteristics of methicillin-resistant S. aureus (MRSA) nasal colonization in Taiwanese children from 2004 through 2009. Risk factors for MRSA were determined for the overall study period.MethodsChildren from birth to ≤14 years of age presenting for health maintenance visits or attending 1 of 57 kindergartens were recruited. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 58 publications
5
24
2
3
Order By: Relevance
“…The ermA and ermC genes are usually the main resistant genes responsible. The ermB gene, formerly found in animal strains conferring constitutive resistance to erythromycin and clindamycin, has recently been observed in human isolates in Taiwan and Hong Kong (Lo et al, 2010). In the current study, the cMLS B phenotype was prevalent in all MLS Bresistant S. aureus isolates and the ermB gene was the most prevalent resistance gene in CA MLS B -resistant S. aureus isolates.…”
Section: Disscussionsupporting
confidence: 51%
“…The ermA and ermC genes are usually the main resistant genes responsible. The ermB gene, formerly found in animal strains conferring constitutive resistance to erythromycin and clindamycin, has recently been observed in human isolates in Taiwan and Hong Kong (Lo et al, 2010). In the current study, the cMLS B phenotype was prevalent in all MLS Bresistant S. aureus isolates and the ermB gene was the most prevalent resistance gene in CA MLS B -resistant S. aureus isolates.…”
Section: Disscussionsupporting
confidence: 51%
“…In the Eritrean cohort, we did not find that healthcare exposure was significantly associated with MRSA nasal carriage, a finding that has been widely reported in the previous literature [2,5,17,18] and in the German cohort of the current study. Due to relatively small sample sizes in this prospective study, associations may not have been detected, particularly for MRSA isolates.…”
Section: Proteus Mirabilis 1 -supporting
confidence: 62%
“…Due to relatively small sample sizes in this prospective study, associations may not have been detected, particularly for MRSA isolates. In contrast, a relatively high prevalence of MRSA colonization was found (11.6%) for a cohort of healthy children aged ≤14 years in community settings in Taiwan over a 5-year period with increasing tendency, despite an overall decrease in the prevalence of nasal colonization by S. aureus [18]. Kuehnert et al [5] concluded that the S. aureus colonization prevalence in the nares was highest in participants 6-11 years old in the United States, whereas MRSA colonization was associated with age ≥60 years and being female but not with recent health-care exposure.…”
Section: Proteus Mirabilis 1 -mentioning
confidence: 77%
“…In our previous studies, high Staphylococcal Enterotoxin B (SEB) gene carriage rate in S aureus was noted. 16,19 In this study, we wanted to find the definite carriage rate of community-associated (CA)-MSSA in Taiwan.…”
mentioning
confidence: 99%